Unfreedom of the press ebook - Levin, Mark R. (2019)
Six-time New York Times bestselling author, FOX News star, and radio host Mark R. Levin "trounces the news media" ( The Washington Times ) in this timely and groundbreaking book demonstrating how the great tradition of American free press has degenerated into a standardless profession that has squandered the faith and trust of the public. Unfreedom of the Press is not just another book about the press. In "Levin's finest work" ( Breitbart ), he shows how those entrusted with news reporting today are destroying freedom of the press from within—not through actions of government officials, but with its own abandonment of reportorial integrity and objective journalism. With the depth of historical background for which his books are renowned, Levin takes you on a journey through the early American patriot press, which proudly promoted the principles set forth in the Declaration of Independence and the Constitution. This is followed by the early decades of the Republic during which newspapers around the young country were open and transparent about their fierce allegiance to one political party or another. It was only at the start of the Progressive Era and the 20th century that the supposed "objectivity of the press" first surfaced, leaving us where we are today: with a partisan party-press overwhelmingly aligned with a political ideology but hypocritically engaged in a massive untruth as to its real nature.